Highly efficient three-dimensional solar evaporator for high salinity desalination by localized crystallization - Wu, Lei (Nat Commun, 2020)
Solar-driven water evaporation represents an environmentally benign method of water purification/desalination. However, the efficiency is limited by increased salt concentration and accumulation. Here, we propose an energy reutilizing strategy based on a bio-mimetic 3D structure. The spontaneously formed water film, with thickness inhomogeneity and temperature gradient, fully utilizes the input energy through Marangoni effect and results in localized salt crystallization. Solar-driven water evaporation rate of 2.63 kg m(−2) h(−1), with energy efficiency of >96% under one sun illumination and under high salinity (25 wt% NaCl), and water collecting rate of 1.72 kg m(−2) h(−1) are achieved in purifying natural seawater in a closed system. The crystalized salt freely stands on the 3D evaporator and can be easily removed. Additionally, energy efficiency and water evaporation are not influenced by salt accumulation thanks to an expanded water film inside the salt, indicating the potential for sustainable and practical applications.